Isolation of immunoreactive proteins from the larval extracts of Boophilus microplus and Hyalomma anatolicum anatolicum - GHOSH, S; KHAN, M H (The Indian Journal of Animal Sciences, 2013)
Crude larval antigens of Boophilus microplus (LEB) and Hyalomma a. anatolicum (LMS) were purified by gel filtration and anion-exchange chromatography to isolate the immunoreactive antigens responsible for induction of resistance. Gel filtration and DEAE-sepharose chromatography of LEB yielded 120 and 76 fractions, respectively, but only one collected by 0.2 M NaCl showed significant precipitation reactions. Similarly, by sephadex G-200 filtration followed by anionexchange chromatography of LMS, an immunoreactive fraction was isolated. Sodium dodecyl sulphate polyacrylamide gel electrophoresis of reactive fractions showed a 68 kDa protein in LEB and 62 and 29 kDa proteins in LMS. The study presents physicochemical procedures for the purification of tick proteins.